Anthropology and Sociology - Korsbaek, Leif (2014)
The article begins with an exploration of sociology´s historical development, always in close connection with the sister discipline of anthropology, rst in the proto sociologists and protoanthropologists, thereafter in the founding fathers, Émile Durkheim, Max Weber and Karl Marx, who are at the same time sociologists and anthropologists. Next comes another scientic triangle: the romantics or neokantians, the scientic functionalists and the Marxists, who curiously coincide in sociology and anthropology as well. Before reaching the conclusion, that suggests that the separation of sociology and anthropology is a separation with an extremely frail foundation, we make two excursions: to an invention that was made at the same time in sociology and anthropology, in the rst discipline named “ethnomethodology”, and in the second “cognitive anthropology”, and the shortlived fashion of postmodernism.